Effects of Artificial Light At Night (ALAN) on the locomotion, anxiety-like and shoaling behaviors of guppies (Poecilia reticulate) - Castillano, Trisha C. (Department of Biology and Environmental Science, College of Science, University of the Philippines Cebu, 2022)
Artificial Light At Night (ALAN) is an increasing anthropogenic pollutant that interferes with the organism¶s circadian rh\thms and disrupts an ecos\stem's natural light and dark c\cle. ALAN induces higher boldness and risk-taking in guppies as an adaptive response to more stressful environments. This study aims to investigate the effects of ALAN on locomotion, anxiety-like behavior, and shoaling behavior in wild-caught guppies (Poecilia reticulata). Guppies were obtained from Bunga River, Oroquieta City, Misamis Occidental. Acute ALAN treatments were administered for 14 days: control (natural daylight at ~1500 lx, night at 0 lx); dim light (natural daylight, 12 hrs ALAN at ~15 lx); and bright light (natural daylight, 12 hrs ALAN at ~1000 lx). Locomotion and anxiety parameters and shoaling behavior parameters were obtained from a Novel Tank Test and a Shoaling Preference Test, respectively. ALAN exposure significantly reduced the total distance traveled in guppies (KruskalWallis: H = 17.6, p = 0.000153). ALAN exposure reduced freezing time in guppies, although the effect is insignificant. ALAN exposure significantly diminished shoaling behavior as guppies exposed to bright ALAN had the greatest latency to the first entry (Kruskal-Wallis: H = 9.18, p = 0.0102) and the least total time spent in the social area (Kruskal-Wallis: H = 6.13, p = 0.0466) compared to the control group. Body sizes of guppies under ALAN exposure were greater, although without statistical significance. Multiple linear regression demonstrates that the variables light treatments, sex, and body depth best predict total distance traveled, sex best predicts freezing time, and light treatments best predict shoaling behavior parameters. Altogether, the present study confirms that ALAN exposure reduces locomotor activity, reduces anxiety-like behavior, diminishes shoaling behavior, and contributes to weight gain in guppies. Circadian rhythm disruption due to ALAN causes behavioral and physiological changes in guppies, which can also negatively affect ecosystem dynamics.